2016
DOI: 10.1016/j.diabres.2015.12.013
|View full text |Cite
|
Sign up to set email alerts
|

c-Abl contributes to glucose-promoted apoptosis via p53 signaling pathway in podocytes

Abstract: c-Abl contributes to high glucose-induced podocyte apoptosis via p53 signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
4
6
0
Order By: Relevance
“…As shown in (Fig. 6F-6G), HG ultimately markedly caused podocyte apoptosis, which was consistent with our previous observation 31. Thus, the results demonstrated that HG stimulated- podocyte injury may be attributed to mitochondrial dysfunction, and AMPK alteration might be involved in the regulatory mechanism.…”
Section: Resultssupporting
confidence: 91%
“…As shown in (Fig. 6F-6G), HG ultimately markedly caused podocyte apoptosis, which was consistent with our previous observation 31. Thus, the results demonstrated that HG stimulated- podocyte injury may be attributed to mitochondrial dysfunction, and AMPK alteration might be involved in the regulatory mechanism.…”
Section: Resultssupporting
confidence: 91%
“…As a component of the glomerular filtration barrier, podocyte apoptosis contributes to the pathogenesis of dKd (24,25). Consistent with previous findings (26), the level of podocyte apoptosis was elevated under HG conditions in the present study ( Fig. 5A and B).…”
Section: Discussionsupporting
confidence: 93%
“…P53 activation was an early signal for cisplatin-induced renal tubular cell apoptosis (17). Our data are consistent with the findings of other studies that p53 mediated high glucose-induced podocyte apoptosis (27). Aldosterone increased p53 expression in rat mesangial cells.…”
Section: Discussionsupporting
confidence: 91%